Urban Shrinkage, Industrial Renewal and Automotive Plants - Luescher, Andreas; Shetty, Sujata; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book focuses on the relationship between the auto industry and the built environment at multiple scales, a topic of particular interest now as the industry is going through a period of major transformation. Drawing from multiple perspectives, including architecture, urban design and urban planning, the authors examine the changing form of the auto factory itself, the changing geography of auto production, and the challenges faced by communities as the auto plants that once brought them prosperity, and often a sense of identity, leave town. They examine four places that are dealing in different ways, and with varying success, with the aftermath of a decommissioned auto plant in their midst. These are Janesville, Wisconsin, and Willow Run, Michigan, in the United States, and Bochum, Germany, and Genk, Belgium, in Europe. Together these four cases provide some clues about what the future might look like for places that were once intimately connected with the manufacture of cars. Sujata Shetty is Interim Director of the Jack Ford Urban Affairs Center and a Professor in the Department of Geography and Planning, at the University of Toledo, Ohio. Andreas Luescher is a Swiss architect, who is currently Professor and Chair of Architecture and Environmental Design at Bowling Green State University in Ohio. .
1. Automotive Production and its Relationship with the Built Environment -- 2. The Packard Plant a Failed American Model of Transformation -- 3: Strategies to Address Decommissioned Automotive Plants -- 4: Examining Transitions in Four Case Studies -- 5: The Future of Automotive Plants. .
Keywords: Sociology, Urban; Human geography; Cultural geography; Economic geography; Urban Sociology; Human Geography; Social and Cultural Geography; Economic Geography